Kebun Raya Bogor Dan Fasilitasnya, Sejarah Dan Fungsi Di Masa Lalu Dan Kini - Deni Sutrisna (Kemendikbud, 2020)
Bogor city is geographically located between mount Gede and mount Salak. High rainfall, the marginal land traversed by the Ci Sadane river and the Ci Liwung river have long been the locations of human activity. Starting from the classical Hindu period (Kerajaan Pakuan Padjadjaran), the colonial period (Dutch and English), and Japan became the destinations of the kingdom’s officials as a Government. The cool air with natural panorama that became the inspiration for the birth of a large garden, called Netherlands Plantentuin te Buitenzorg (Bogor Botanical Garden) with various facilities in the period 18-19 AD century visiting people at home and abroad. How the history of botanical garden and its facilities in the past and presents the questions discussed in this paper. To meet the needs of the data needed to use the method of library study and observation of physical data in field about the building both the environment. The results of the analysis from the two sources show that Bogor Botanical Gardens is still working as a research site for plants and a resting place for state officials for a long time. In addition, the botanical garden is now also used as a city lung and recreation area.